2016
DOI: 10.1016/j.tjo.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the vascular theory of glaucomatous optic nerve degeneration

Abstract: An understanding of the pathogenesis of glaucoma is one of the foundations in glaucoma management. A number of theories have been presented to explain glaucomatous neural degeneration. The vascular theory attempts to explain the causation of glaucoma on the basis of vasogenic factors and altered he-modynamics in the body; however, this theory remains controversial. There are proponents for and against the role played by vascular factors in the development of glaucomatous optic nerve degeneration. This review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 40 publications
(85 reference statements)
1
33
0
2
Order By: Relevance
“…Several theories have been proposed to explain the glaucomatous optic nerve degeneration [29]. Endogenous NO signaling within the conventional outflow pathway is one of the key mediators of outflow regulation and maintenance of physiological levels of IOP [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theories have been proposed to explain the glaucomatous optic nerve degeneration [29]. Endogenous NO signaling within the conventional outflow pathway is one of the key mediators of outflow regulation and maintenance of physiological levels of IOP [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in NO signaling or reduced NO production in part may result in impaired trabecular outflow and contribute to IOP elevation in POAG [10,13]. Likewise, the role of eNOS/NO pathway in the maintenance of ocular vasculature and optic nerve degeneration is also highly critical [29]. Notably, functional polymorphisms in the NOS3 gene that alter eNOS function/ activity have been described in various complex diseases, including glaucoma [21].…”
Section: Discussionmentioning
confidence: 99%
“…S. Zavadskaya and G. G. Karzhaubaeva, this is due to a deficiency of tocopherol, one of the leading endogenous antioxidants. The metabolic mechanisms involved in the occurrence and development of glaucoma also include pseudoexfoliative dystrophy in the anterior segment of the eye and impaired glycosaminoglycans metabolism (Ahmad 2016).…”
Section: Theories Of Glaucoma Pathogenesismentioning
confidence: 99%
“…Indeed, it has been shown that during chronic glaucoma, the apoptosis, hypoxia and oxidative stress phenomena were correlated with the progression of the disease [17] [19] [78]. These would intensify to give way to the necrosis of the retinal cells ganglion, then in fine, those of the head of the optic nerve [12] [83]. However, the presence of higher CmNgb and CmCyt C in CG + compared to CG − made us accept the hypothesis that the absence of correlation found between CmCyt C and CmNgb is would be due to the anti-apoptotic activity of the Ngb.…”
Section: Relationship Between Cmngb Cmcyt C and Cmgpx In Cg +mentioning
confidence: 99%
“…The first is mechanical, and has the major effect of compression of the head of the optic nerve by intra-eye hyper pressure. The second, is vascular, and involves hypoperfusion and ischemia-hypoxia of the optic nerve [12]- [18]. Despite these theories, only intra ocular pressure (IOP) remains the commonly modified risk factor during glaucoma.…”
Section: Introductionmentioning
confidence: 99%